Expanding the notion of personal well-being during covid-19 campus closure in India: results from a mixed-methods study with members of higher education - Yeon, G.; Perumbilly, S.; Elangovan, N.; Awungshi, S.; Varghese, K.J. (Asia Pacific Journal of Educators and Education, 2024)
The COVID-19 pandemic has challenged lives globally in unprecedented ways. While numerous studies have discussed the impact of this pandemic on human lives, this descriptive study examined how this pandemic affected personal well-being (PW) for members of Indian higher education in the early phase of the pandemic in 2020 when there were no vaccines and remedies available. Research participants (n = 551) were faculty members, graduate students, and non-teaching staff in Indian higher education. At the time of data collection, when all campuses were closed, all participants were functioning in their roles in the academic communities via virtual platforms. This descriptive study, based on a mixed-methods research design with concurrent triangulation strategies, collected data from all regions of India. Resulting data identified and discussed the impact of the pandemic on six domains of PW in the life of participants: (a) self-care; (b) professional growth; (c) quality of interrelationship within the family; (d) relationships with significant others outside of the family; (e) process of experiencing/facing and addressing challenges; and, (f) relationship with spirituality/transcendental dimensions. The relevance of the last domain may be unique to Indian participants’ socio-cultural context and ethos. The findings and discussion explain how PW is a composite of all these six domains, and the pandemic expanded the notion of PW for the members of Indian higher education. Further, the findings also provided a general orientation on how educational leadership teams and institutions can enhance at least three specific dimensions of their community members and thus increase the likelihood of improving the quality of their professional and personal life. The findings may also have relevance for academic communities worldwide and inform clinicians working with members of academic communities, educational institutions, and policymakers. © Penerbit Universiti Sains Malaysia, 2024.
Keywords: Teacher leadership; dept.mft; distributed leadership; middle leaders; middle leadership; peer-reviewed; teacher leaders

Desire on the Inside: Incarcerated bisexual women, identity, and human connection - Smoyer, Amy; Harvey, Rebecca (Queering Desire: Lesbians, Gender and Subjectivity, 2024)
Queering Desire explores, with unprecedented interdisciplinary scope, contemporary configurations of lesbian, bi, queer women’s, and non-binary people’s experiences of identity and desire. Taking an intersectional feminist and trans-inclusive approach, and incorporating new and established identities such as non-binary, masculine of centre (MOC), butch, and femme, this collection examines how the changing landscape for gender and sexual identities impacts on queer culture in productive and transformative ways. Within queer studies, explorations of desire, longing, and eroticism have often neglected AFAB, transfeminine, and non-binary people’s experiences. Through 25 newly commissioned chapters, a diverse range of authors, from early career researchers to established scholars, stage conversations at the cutting edge of sexuality studies. Queering Desire advances our understanding of contemporary lesbian and queer desire from an inclusive perspective that is supportive of trans and non-binary identities. This innovative interdisciplinary collection is an excellent resource for scholars, undergraduate, and postgraduate students interested in gender, sexuality, and identity across a range of fields, such as queer studies, feminist theory, anthropology, media studies, sociology, psychology, history, and social theory. In foregrounding female and non-binary experiences, this book constitutes a timely intervention.
Keywords: dept.mft; dept.swk; peer-reviewed